The effects of SPIR Interventions on nutrition and childcare: Evidence from the SPIR midline survey - Alderman, Harold; Gilligan, Daniel O.; Hidrobo, Melissa; Leight, Jessica; Tambet, Heleene (International Food Policy Research Institute, 2020)
Ethiopia has made major strides in improving nutrition in the past two decades; the prevalence of stunting decreased considerably from 58% in 2000 to 38% in 2016 and further to 37% in 2018.1 While there is no consensus on the underlying causes of this improvement—although substantial increases in income and education surely contributed—there is consensus that more must be done to maintain the momentum. In particular, a number of infant and young child feeding (IYCF) practices can be improved. While breastfeeding initiation is nearly universal, many children are not exclusively breastfed until they are 6 months old, which is the recommended practice. Similarly, few children age 6–23 months meet the minimum acceptable dietary standards. This brief presents evidence on the impact of the SPIR project on key IYCF practices at the time of the midline survey.